A multilocus evaluation of ermine (Mustela erminea) across the Holarctic, testing hypotheses of Pleistocene diversification in response to climate change. (31st October 2013) - Dawson, Natalie G.; Hope, Andrew G.; Talbot, Sandra L.; Cook, Joseph A.; Rocha, Luiz
Abstract Aim We examined data for ermine (Mustela erminea) to test two sets of diversification hypotheses concerning the number and location of late Pleistocene refugia, the timing and mode of diversification, and the evolutionary influence of insularization. Location Temperate and sub‐Arctic Northern Hemisphere. Methods We used up to two mitochondrial and four nuclear loci from 237 specimens for statistical phylogeographical and demographic analyses. Coalescent species‐tree estimation used a Bayesian approach for clade divergence based on external mutation rate calibrations. Approximate Bayesian methods were used to assess population size, timing of divergence and gene flow. Results Limited structure coupled with evidence of population growth across broad regions, including previously ice‐covered areas, indicated expansion from multiple centres of differentiation, but high endemism along the North Pacific coast (NPC). A bifurcating model of diversification with recent growth spanning three glacial cycles best explained the empirical data. Main conclusions A newly identified clade in North America indicated a fourth refugial area for ermine. The shallow coalescence of all extant ermine reflects a recent history of diversification overlying a deeper fossil record. Post‐glacial colonization has led to potential contact zones for multiple lineages in north‐western North America. A model of diversification of ermine accompanied by recent gene flow was marginally less well supported than a model of divergence of major clades in response to the most recent glacial cycles.